Analisis pertumbuhan ekonomi terhadap ketimpangan pendapatan masyarakat di provinsi riau - Yunita, Vebby; Kadir, Hainim; ', Harlen (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
Riau economic growth rate may be an indicator of the increasing level of economic development, which in turn will increase the level of social welfare. One characteristic of the increasing development is increasingly unequal distribution level. However, it appears that the more unequal distribution of income levels, whereas the level of income distribution is needed to support the sustainability of economic growth. Therefore, this study aims to describe the general level of economic growth, the level of income distribution among the public, as well as the relationshipbetween multiple levels of economic growth on income distribution in the province of Riau. To achieve the first objective used descriptive and analytical tools used for both purposes of data analysis tools panel fixed effect model using STATA 9. From the analysis shows economic growth still high despite a slowdown, the economic structure changes from the primary sector to the secondary and tertiary sectors. The bigger income inequality in Riau Province which is characterized by Gini ratio in 2012, which reached 0:40. From the regression results shown that significant economic growth effect on income inequality. . The higher rate of economic growth, the higher the level of inequality of income communities in Riau province, although in a lower category. Economic growth has a considerable influence on the increase in the Gini ratio Riau Province, it is seen from the value of the elasticity of 0.882666, meaning that a 1 percent change in economic growth would raise the Gini ratio of 0.882666 percent.Keywords: economic growth, income distribution, panel data